Investigation of a Digital Hydraulic Valve Operated by Servo Motors - Ozalp, A. F.; Polat, R.; Cetinkaya, C.; Cetin, M. H. (Engineering, Technology & Applied Science Research, 2021)
This paper describes a new type of digital hydraulic valve run by two servo motors. Digital hydraulics is a cutting-edge technology, which saves more exhausted energy than conventional hydraulic valves. It includes conventional valves, but its working principle is different. Similar or different size valves constitute a digital hydraulic valve assembly. When the assigned valves are opened, a certain amount of flow is obtained from the output of the valve assembly. To control a digital hydraulic valve, Pulse Number Modulation (PNM) Control technique is used for equal valve flow rates, while Pulse Code Modulation (PCM) is used for different valve flow rates. Valves are exerted by independently launched electric coils. Previous studies used controller board and external power booster circuits for coils. In this study, a new type of digital hydraulic valve is designed, manufactured, and tested with the PNM method. The studied valve body has two different valve groups. Every group includes 16 equal valves and 1 camshaft rotated by 1 servo motor. The servo motors are controlled by a PLC. The calculated performance index is found to be 5.1ms which is similar to the results of previous studies. The experimental results showed that the cam and servo motor controlled digital hydraulics is applicable to variable speed control hydraulic systems.